Spring the story of Hsu Chin-yu - Government Information Office; Public Television Service (Taiwan : Public Television Service, 2000)
During the White Terror of the 1950s many patriotic young Taiwanese were arrested by the Nationalist Government. They were accused being'bandits','communist', or'traitor'. Those executed or imprisoned numbered in the tens of thousands. One victims was Hsu Chin-yu, an adopted daughter of an ordinary Taipei family. She began working at the age 14. She subsequently spent 15 years in prison and her life would never be the same
Executive producer, Sylvia Feng ; director, Tseng Wen-Chen ; producer, Yu Ching-ping
DVD format
Subtitles in Traditional English, English, Francais and Espanol
Keywords: Chin-yu, Hsu; Taiwan -- Politics and government -- 1945-1975; Taiwan -- History -- 1945-